Politik Representasi Aisyiyah dalam Pilkada Serentak Kabuapten Ponorogo Tahun 2020 - Prihatin, Novita Setyo; Sulton, Sulton; Asmaroini, Ambiro Puji (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
This study examines the Politics of Representation in the Simultaneous Pilkada of Ponorogo Regency in 2020. The subject of this research is the Aisyiyah organization to reveal how the representation and control of Aisyiyah Politics in the simultaneous Pilkada in Ponorogo Regency in 2020. The primary data was obtained/sourced from the Aisyiyah administrators using the method of interviews while secondary data in the form of documents about Aisyiyah's activities were collected using the documentation method. The collected data is then processed and analyzed using the Huberman-Milles interactive analysis model. Based on this analysis, it was found that many organizations want the implementation of the 2020 simultaneous elections in the Ponorogo Regency to run healthily. One of the organizations that decided to actively participate was from the women's group, Aisyiyah. Aisyiyah's political representation has become resilient in the political field for women. Aisyiyah's embodiment is to strengthen the presence of women in the 2020 simultaneous elections in Ponorogo, namely by being a political representation and controlling the implementation of the 2020 simultaneous elections in depth.